REGIONALIZATION OF MONTHLY PRECIPITATION VALUES IN THE STATE OF PARANÁ (BRAZIL) BY USING MULTIVARIATE CLUSTERING ALGORITHMS - Pansera, Wagner Alessandro; Gomes, Benedito Martins; Vilas Boas, Marcio Antonio; Queiroz, Manoel Moises Ferreira de; Mello, Eloy Lemos de; Sampaio, Silvio Cesar (IRRIGA, 2015)
REGIONALIZATION OF MONTHLY PRECIPITATION VALUES IN THE STATE OF PARANÁ (BRAZIL) BY USING MULTIVARIATE CLUSTERING ALGORITHMS WAGNER ALESSANDRO PANSERA1; BENEDITO MARTINS GOMES2; MARCIO ANTONIO VILAS BOAS2; SILVIO CESAR SAMPAIO2; ELOY LEMOS DE MELLO2 E MANOEL MOISES FERREIRA DE QUEIROZ3 1 Departamento de Construção Civil, Universidade Tecnológica federal do Paraná (UTFPR), Pato Branco-PR, e-mail:pansera@utfpr.edu.br 2 Centro de Ciências Exatas e Tecnológicas, Universidade Estadual do Oeste do Paraná (UNIOESTE), Cascavel-PR. e-mail:benedito.gomes@unioeste.br, marcio.vilasboas@unioeste.br, silvio.sampaio@unioeste.br, eloy.mello@unioeste.br 3 Centro de Ciências e Tecnológica Alimentar, Universidade Federal de Campina Grande (UFCG), Pombal-PB. e-mail: moises@ccta.ufcg.edu.br. 1 ABSTRACT Rainfall is one of the most important factors in agricultural water management, especially to land farming of Paraná. Regionalization of rainfall data is useful for optimum design of projects and management of water related activities. Therefore, the objectives of this study were to evaluate the potential of multivariate clustering methodologies to identify homogenous regions using time series of monthly precipitation as the classification variable; the quality of the formed regions and estimate precipitation quantiles. k-means, hierarchical and hybrid clustering techniques were used. The rainfall stations in each group were subjected to metrics of homogeneity. The Paraná state could be subdivided into six homogeneous regions of monthly precipitation using the hybrid methodology between k-means and Ward. Keywords: regional frequency analysis, L-moments, cluster analysis PANSERA, W. A.; GOMES, B. M.; VILAS BOAS, M. A.; SAMPAIO, S. C; MELLO, E. L. DE; QUEIROZ, M. M. F. DE. REGIONALIZAÇÃO DE VALORES DE PRECIPITAÇÃO MENSAL NO ESTADO DO PARANÁ (BRASIL) USANDO ALGORITMOS DE AGRUPAMENTOS MULTIVARIADOS 2 RESUMO A chuva é um dos fatores mais importantes na gestão da água na agricultura, especialmente para o estado do Paraná-BR. A regionalização de dados de chuva é útil para otimização de projetos e gestão das atividades relacionadas com a água. Portanto, este estudo teve por objetivo avaliar as metodologias multivariadas de agrupamentos para identificar regiões homogêneas usando as séries históricas de precipitação mensal como variável classificatória, avaliar a qualidade das regiões formadas e estimar quantis de precipitação. As técnicas de agrupamento utilizadas foram: k-médias, hierárquico e híbrido. As estações pluviométricas presentes em cada grupo foram submetidas às métricas de homogeneidade e discordância. Foi possível subdividir o estado Paraná em seis regiões homogêneas de precipitação mensal utilizando a metodologia hibrida entre k-médias e Ward. Palavras-chave: Análise de frequência regional, momentos-L, análise de agrupamentos.